2015
DOI: 10.3892/mco.2015.648
|View full text |Cite
|
Sign up to set email alerts
|

Promoter mutation of tumor suppressor microRNA-7 is associated with poor prognosis of lung cancer

Abstract: Abstract. The significance of promoter mutations of microRNAs (miRNAs) in lung cancer is poorly understood. Recent evidence demonstrated that miRNA-7 (miR-7), a unique member of the miRNA family, exhibited decreased expression and has emerged as an important regulator in lung tumorigenesis. However, the mechanism underlying the downregulation of miR-7 in lung cancer remains largely unknown. In this study, we investigated the sites of mutation of the miR-7 promoter in lung cancer tissues using DNA sequencing. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 28 publications
4
20
0
Order By: Relevance
“…As shown in Figure 1D, the proliferation of human lung cancer cell line 95D cells decreased significantly in the p-T-miR-7-transfected group (p < 0.05). Moreover, the colon-formation ability of cells was also impaired unmistakably (Figure 1E; p < 0.05), which was consistent with our previous works 17, 18. To confirm this finding, we also detected the expression of cell-growth-related factors such as CDK2, CDK3, CDK4, and CDK6 in lung cancer cells.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…As shown in Figure 1D, the proliferation of human lung cancer cell line 95D cells decreased significantly in the p-T-miR-7-transfected group (p < 0.05). Moreover, the colon-formation ability of cells was also impaired unmistakably (Figure 1E; p < 0.05), which was consistent with our previous works 17, 18. To confirm this finding, we also detected the expression of cell-growth-related factors such as CDK2, CDK3, CDK4, and CDK6 in lung cancer cells.…”
Section: Resultssupporting
confidence: 91%
“…Consistently, our previous work also showed that overexpression of miR-7 could reduce the growth and metastasis of human lung cancer cells in vivo and in vitro 17 . Moreover, the reduced expression of miR-7 was associated with the sites mutation of its promoter region in lung cancer tissues, indicating that miR-7, an important tumor suppressor, could be used as candidate for targeted gene therapy against lung cancer 18, 19…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…It has been reported that downexpression of miR-7 in NSCLC may be implicated in promoting cancer cell progress, and consequently results in NSCLC growth [19, 24], which were in line with our study results. In addition, miR-7 is a tissue-specific miR to be directly involved in NSCLC [25].…”
Section: Discussionsupporting
confidence: 93%